Intruder Detection Monitoring System in Computer Networks Using Snort Based Sms Alert (Sistem Monitoring Deteksi Penyusup Dalam Jaringan Komputer Menggunakan Snort Berbasis Sms Alert) - Heri Yanto; Febri Hadi (Jurnal KomtekInfo, 2020)
Network security is an important factor in guaranteeing data. Guaranteed security can avoid losses caused by attacks that occur in the network. Administrators play an important role in maintaining data or file security, but administrators cannot at all times monitor the security of the network. This problem can be overcome by adding a system for data traffic detection or called IDS. IDS will be linked by SMS Alert so that administrators can receive notifications of interruptions on the network. In this study, researchers conduct analysis and testing of problems that arise so that it will produce a system that is able to detect attacks or disruptions on the network quickly and can provide warnings to network administrators, so that administrators can take steps to anticipate these disruptions. Attacks can be detected from the pattern of attacks that are in the IDS rule so that intruders who try to enter will be detected and the system will send an SMS notification to the administrator.